FAKTOR YANG MEMPENGARUHI E-BANKING READINESS PENGGUNA E-BANKING DI JAKARTA - Anthony, Hendro Lukman (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
This research aims to obtain empirical evidence about factorsthat affecting interest in using E-banking services in Jakarta. This research uses primary data obtained using questionnaire distributed to E-banking users in Jakarta. The population of this research is E- banking users in Jakarta. This research is conducted with a sample of 110 data. Furthermore, data collection techniques used in this research is primary data that is processed using Statistical Package for the Social Sciences (SPSS) ver 21.0 software. The statistical method used to test the hypothesis is the multiple linear regression method. The results of this research show that factors such as usefulness, ease of use, convenience, and security and privacy has significant effect on interest in using E-banking services.